Effects of two non-drug interventions on pain and anxiety in the nursing process of burn patients: a literature review with meta-analysis - Wei Zhang; Xiaona Sui; Lingling Zhang; Liping Zhang; Huilan Yan; Shuangshuang Song (Frontiers Media S.A., 2024)
BackgroundBurns are a global health issue causing significant mortality and high medical costs. Non-pharmacological interventions such as music therapy and virtual reality (VR) therapy have shown potential in alleviating pain and anxiety in burn patients. This study systematically evaluates the impact of these interventions using a network meta-analysis.MethodsA systematic review and network meta-analysis were conducted according to PRISMA 2020 guidelines and registered in PROSPERO (CRD42024566536). Searches in PubMed, Cochrane Library, Web of Science, and Embase up to November 22, 2023, identified randomized controlled trials (RCTs) involving music therapy or VR therapy in burn patients. The Cochrane Risk of Bias Tool (2.0) assessed study quality. Data were analyzed using StataMP-64 software.ResultsSeventeen RCTs with 1,119 burn patients were included. Both music therapy and VR therapy significantly reduced pain and anxiety compared to control groups. Music therapy was more effective for pain reduction (SUCRA: 85.4%), while VR therapy was superior for anxiety relief (SUCRA: 79.5%).ConclusionMusic therapy and VR therapy effectively reduce pain and anxiety in burn patients. Integrating these interventions into burn care can enhance patient outcomes. Further research is needed to confirm these findings and optimize individualized treatment plans.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO (CRD42024566536).